Temporal and spatial characteristics of flocculated suspended solids in a deep reservoir an in situ observation in the Biliuhe Reservoir - Liu, Yuyu (Environmental technology, 2023)
The amount of total suspended solids (TSS) is the most visible indicator for evaluating water quality in reservoirs. Previous investigations paid more attention to TSS of the surface layer in reservoirs, while suspended particles are prone to settle, resuspend, and aggregate at the bottom of reservoir. There may be different patterns of the TSS in different depths. This study is to assess the TSS concentration by weight analysis, find the evidence of the existence of flocculated suspended particles by in situ underwater imaging analysis, and discuss the impact of the flocculation process of suspended solids on water quality in deep reservoirs. Although the TSS concentration is lower than other reservoirs with the same trophic level, many flocs were found at the bottom of the deep-water area (> 15 m) in the Biliuhe Reservoir according to the recordings of the in situ underwater camera. The further comprehensive analysis demonstrates that the fine particle in flood season and resuspension is the main source of suspended flocs at the bottom of the reservoir. While the slow settling velocity results in the flocculation of fine suspended particles and long-term residence in the bottom layer of the reservoir. TSS has a significant correlation with iron and total phosphorus. Resuspension, flocculation, and settling impact on the transport of suspended sediment and associated contaminants. The evidence from this study suggests that the impact of flocs on water quality should be further discussed to ensure water supply safety